DETERMINACIÓN DE ENTEROBACTERIACEAE PROCEDENTES DE LOS MOLUSCOS, Gari solida “almeja blanca” y Aulacomya ater “choro” QUE SE EXPENDEN EN EL TERMINAL PESQUERO DE BUENOS AIRES, VICTOR LARCO, TRUJILLO. - ZAVALETA OTINIANO, Stefanny Katherine (2019)
The presence of enterobacteriaceae was determined through bacteriological study in two species of bivalve molluscs used in human food, Gari solida "clam" and Aulacomya ater "choro"; obtained at random from different establishments inside the "Mercado Mayorista" Fishing Terminal of Buenos Aires, located in the District of Víctor Larco, Province of Trujillo, Department of La Libertad. The study of the samples was carried out in a macroscopic observation, a bacteriological study of the edible part; and a biochemical study, to then perform the serological study for the determination of the enterobacteriaceae at the level of genus and species present in the molluscs. The species Klebsiella sp., Enterobacter sp., Citrobacter sp., Escherichia coli and Salmonella enteritidis were found in the bivalve molluscs analyzed. 100% of the samples evaluated showed contamination by Proteus sp.